Method Development and Validation of Ephedrine and Pseudoephedrine in Horse Urine by Liquid Chromatography-Tandem Mass Spectrometry - Maurya, Ashok Kumar; Sahu, Puran Lal; Jethi, Sakshi; Gosain, Himank; Sahu, Kapendra (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: A comprehensive, fast and precise method for the quantification of ephedrine and pseudoephedrine in horse urine was established and validated utilizing Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) followed by the necessities of Association of Official Racing Chemists (AORC), Federation of Equine International (FEI) and International Council for Harmonization (ICH) guidelines. Methodology: The processing of samples was performed by de conjugation accompanied by enzymatic hydrolysis, Solid Phase Extraction (SPE) procedure using HLB cartridges. Results: The total chromatographic run time of this method was 7.0 min and found linear over the concentration range of 4-40 ng/mL with a correlation of coefficient (r2) of 0.99. The intraday and inter-day assay precision of ephedrine were extended from 1.64 to 2.86% and 1.61 to 3.12 %, respectively. In context of pseudoephedrine, the intraday and interday assay precision were ranged from 1.55 to 3.26% and 1.11 to 2.60 %, respectively. The absolute percent recovery (%) was found to be 85% for Ephedrine and 90% for Pseudoephedrine. The percent recovery was adequate to discriminate and quantitate the Ephedrine and Pseudoephedrine at or below the level prescribed by AORC Proficiency Testing (PT) list ie 20ng/ ml for equine urine sample. The LOD and LOQ were found 2 and 4 ng/ml respectively for Ephedrine and Pseudoephedrine. Conclusion: A comprehensive and precise method for quantitative estimation and diastereomeric differentiation of Ephedrine and Pseudoephedrine by LC-MS/MS was well established and validated according to AORC, FEI and ICH guidelines. This strategy may be additionally utilized for remedial medication checking purposes.
Keywords: Ephedrine; Pseudoephedrine; ICH Guidelines; Doping control; Mass; spectrometry; AORC; Validation